Presentación de libro: Investigar y escribir con APA 7 - Dennis, Arias Chávez (2021)
Autor: Dennis Arias Chávez (Perú); Autor: Luis Miguel Cangalaya Sevillano (Perú) ; Panelista: Miguel Inga (Perú) ; Panelista: Jesús Raymundo (Perú) ; Moderadora: Lía Castillo (Perú)